Challenges and prospects of sustainable groundwater management in the Indus Basin, Pakistan - Qureshi, A.S.; McCornick, Peter G.; Sarwar, A.; Sharma, Bharat R. (Springer, 2010)
In Pakistan, on-demand availability of groundwater has transformed the concept of low and uncertain crop yields into more assured crop production. Increased crop yields has resulted in food security and improved rural livelihoods. However, this growth has also led to problems of overdraft, falling water tables and degradation of groundwater quality, and yields generally remain well below potential levels. Over the last three decades, Pakistan has tried several direct and indirect management strategies for groundwater management. However the success has been limited. This paper argues that techno-institutional approaches such as introducing water rights, direct or indirect pricing and permit systems are fraught with difficulties in Pakistan due to its high population density and multitude of tiny users. Therefore there is a need to develop frameworks and management tools that are best suited to Pakistani needs. Pakistan should follow both supply and demand management approaches. For demand management, adoption of water conservation technologies, revision of existing cropping patterns and exploration of alternate water resources should be encouraged. For supply management, implementation of the groundwater regulatory frameworks developed by Provincial Irrigation and Drainage Authorities (PIDAs) and introduction of institutional reforms to enhance effective coordination between different organizations responsible for the management of groundwater resources should be given priority.